Promoting Indonesian Moderate Islam on the Global Stage: Non-State Actors’ Soft Power Diplomacy in the Post-New Order Era - Nubowo, Andar (Universitas Islam Internasional Indonesia (UIII), 2023)
This paper investigates why and how Muhammadiyah and Nahdlatul Ulama (NU) have engaged in the soft power diplomacy of Islam in post-Suharto Indonesia and how they mobilise their vast resources and networks to do so. The nefarious effects of radical extremism have invited the Muslim world, including Indonesia, to revert to the notion of Islamic moderation, a justly balanced Islam (wasatiyyat Islam), and to promote it nationally and globally. In this sense, both state and non-state actors, such as Muhammadiyah and NU, have pulled themselves into soft power diplomacy. Drawing upon the lens of soft power and public diplomacy theory, this paper finds that Muhammadiyah and NU’s involvement in Indonesia’s soft power and public diplomacy is generated by shared interests in reinstalling a moderate identity at home and abroad. In this vein, through dialogues, cooperation, humanitarian action, and the establishment of special branches and sister organisations, the two most prominent Islamic institutions in Indonesia have attempted to internationalise the best practice of Indonesian Islam, rooted sociologically and historically in tolerance, openness, and temperance. This paper discovers that, although confronted by some weaknesses and challenges, Muhammadiyah and NU constantly attempt to craft global networks of moderate Islam and to recenter Indonesian Islam as a new centre of Islamic civilisation.